Comparing Surgical Approaches for Thumb Polydactyly Reconstruction in Wassel Type IV: K-wire Fixation Versus Non-K-wire Fixation - Chi Peng, MD; Che-Hsiung Lee, MD; Shih-Heng Chen, MD; Ren-Wen Huang, MD; Cheng-Hung Lin, MD; Yu-Te Lin, MD, MSc, FACS; Chung-Chen Hsu, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Wassel type IV is a common radial polydactyly anomaly characterized by duplication of the proximal phalanges at the metacarpophalangeal joint (MPJ). The primary goal of reconstructive surgery is to achieve a fully functional thumb with appropriate mobility, dimensions, and stable MPJ. This study aimed to compare the outcomes of MPJ reconstruction using either K-wire or non-K-wire fixation for Wassel type IV polydactyly. Methods:. The study included 78 thumbs from 77 patients with Wassel Type IV polydactyly between April 2011 and December 2022. In addition to standard excision of duplicates, MPJ collateral ligament repair, and thenar muscle reattachment using a periosteal sleeve flap, the study analyzed the application of tendon transfer, soft-tissue augmentation, and K-wire fixation. Outcomes were evaluated using Tada score classification, MPJ deviation angle, and range of motion. Complications were also documented. Results:. There was no significant difference in surgical outcomes based on Tada classification between the K-wire and non-K-wire fixation groups. Favorable outcomes were achieved in 76.3% and 84.2% of the K-wire and non-K-wire fixation groups, respectively. Although there was a significantly higher tissue augmentation rate in the K-wire fixation group, there were no significant differences in preoperative and postoperative MPJ angles between the 2 groups. Complications associated with K-wire fixation included pin tract infection (10.2%), migration (10.2%), and maceration (5.1%). Conclusions:. Both K-wire and non-K-wire fixation approaches for Wassel type IV polydactyly yielded favorable subjective and objective outcomes. However, complications associated with K-wire fixation should be considered when determining the surgical approach.